2012
DOI: 10.1242/jeb.062075
|View full text |Cite
|
Sign up to set email alerts
|

Salinity- and population-dependent genome regulatory response during osmotic acclimation in the killifish (Fundulus heteroclitus) gill

Abstract: SUMMARYThe killifish Fundulus heteroclitus is abundant in osmotically dynamic estuaries and it can quickly adjust to extremes in environmental salinity. We performed a comparative osmotic challenge experiment to track the transcriptomic and physiological responses to two salinities throughout a time course of acclimation, and to explore the genome regulatory mechanisms that enable extreme osmotic acclimation. One southern and one northern coastal population, known to differ in their tolerance to hypo-osmotic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
129
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(145 citation statements)
references
References 100 publications
15
129
1
Order By: Relevance
“…This is surprising given the fact that the synthesis of myo-inositol phosphate from G-6-P is the more rate-limiting step of the MIB pathway (Majumder et al, 1997), but does agree with a previous study that compared the regulation of the two enzymes (Sacchi et al, 2013). Significant upregulation or downregulation of IMPA1 mRNA under hyper-and hypo-osmotic challenge, respectively, has been reported in other teleost fishes (Evans and Somero, 2008;Kalujnaia et al, 2010;Whitehead et al, 2012). In leopard sharks, an osmoconforming species, inositol-related proteins have also been reported to be regulated in rectal gland and gill tissues in response to hypo-osmotic challenge (Dowd et al, 2010).…”
Section: Mib Enzymes In Tilapia Brain Robustly Respond To Plasma Osmosupporting
confidence: 86%
“…This is surprising given the fact that the synthesis of myo-inositol phosphate from G-6-P is the more rate-limiting step of the MIB pathway (Majumder et al, 1997), but does agree with a previous study that compared the regulation of the two enzymes (Sacchi et al, 2013). Significant upregulation or downregulation of IMPA1 mRNA under hyper-and hypo-osmotic challenge, respectively, has been reported in other teleost fishes (Evans and Somero, 2008;Kalujnaia et al, 2010;Whitehead et al, 2012). In leopard sharks, an osmoconforming species, inositol-related proteins have also been reported to be regulated in rectal gland and gill tissues in response to hypo-osmotic challenge (Dowd et al, 2010).…”
Section: Mib Enzymes In Tilapia Brain Robustly Respond To Plasma Osmosupporting
confidence: 86%
“…Scott et al (2004) reported F. heteroclitus population divergence in Cl − regulation following freshwater challenges. However, previous high-salinity challenges showed no loss of osmolyte balance and no difference between northern and southern populations (Scott et al, 2008;Scott and Schulte, 2005 (Whitehead et al, 2012b). Thus, we find that osmotic challenges spanning the salinity threshold across which gills are remodeled (∼1 p.p.t.)…”
Section: Results and Discussion Physiological Acclimationmentioning
confidence: 47%
“…Other killifish studies have contrasted Atlantic coastal populations from northern and southern regions, where the FW-native population shows greatest genetic similarity to fish from the northern clade in both nuclear (Duvernell et al, 2008) and mitochondrial (Whitehead, 2009) markers. Northern fish display improved ability to maintain internal ion homeostasis in response to low salinity challenge compared with southern fish (Whitehead et al, 2012b;Scott et al, 2004).…”
Section: Results and Discussion Physiological Acclimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, even intraspecific differences in the response to environmental stressors exist, and likely influence the response to crude oil [31]. Killifish populations on the East Coast of the US have variable responses to thermal and salinity stress [32] [33], and some have developed a resistance to PAH teratogenicity, and toxicity in adults [34] [35]. RECOVER physiologists and collaborators in the ecological and molecular sciences are using populations of Fundulus grandis found along the Gulf of Mexico coast to better understand how a species of fish may react differently to PAH exposure from oil based on their respective exposure histories.…”
Section: Understanding Pah Resistance In Fishesmentioning
confidence: 99%